Molecular Epidemiology of Hemoglobinopathies in Cambodia. (3rd May 2016) - Munkongdee, Thongperm; Tanakulmas, Jatuporn; Butthep, Punnee; Winichagoon, Pranee; Main, Barbara; Yiannakis, Miriam; George, Joby; Devenish, Robyn; Fucharoen, Suthat; Svasti, Saovaros
Abstract: Determining the magnitude of the thalassemia problem in a country is important for implementing a national prevention and control program. In order to acquire accurate thalassemia prevalence data, the gene frequency of α- and β-thalassemia (α- and β-thal) in different regions of a country should be determined. The molecular basis of thalassemia in Cambodia was performed by polymerase chain reaction (PCR)-based techniques in a community-based cross-sectional survey of 1631 unrelated individuals from three regions, Battambang, Preah Vihear and Phnom Penh. Thalassemia mutations were detected in 62.7% of the three studied population of Cambodia. Hb E ( HBB : c.79G > A) was the most common β-globin gene mutation with a frequency ranging from 0.139 to 0.331, while the most frequent α-globin gene mutation was the –α 3.7 (rightward) deletion (0.098–0.255). The other frequencies were 0.001–0.003 for β-thal, 0.008–0.011 for α-thal-1 (– – SEA ), 0.003-0.008 for α-thal-2 [–α 4.2 (leftward deletion)], 0.021–0.044 for Hb Constant Spring (Hb CS, HBA2 : c.427T > C) and 0.009–0.036 for Hb Paksé ( HBA2 : c.429A > T). A regional specific thalassemia gene frequency was observed. Preah Vihear had the highest prevalence of Hb E (55.9%), α-thal-2 (24.0%) and nondeletional α-thal (15.1%), whereas Phnom Penh had the lowest frequency of thalassemia genes. Interestingly, in Preah Vihear, the frequency of Hb Paksé was extremely high (0.036), almost equivalent to that of Hb CS (0.044). Our results indicate the importance of micromapping and epidemiology studies of thalassemia, which will assist in establishing the national prevention and control program in Cambodia.